Exploring the Anti-Inflammatory Mechanism of Tieguanyin (TGY) Volatile Compounds Based on Gas Chromatography-Mass Spectrometry (GCMS)- Network Pharmacology - Qin, Ping; Wang, Xiangpei; Ding, Qin; Zhang, Mei; Wu, Hongmei (Combinatorial Chemistry & High Throughput Screening, 2022)
Background and Objective: Inflammation is a common disease which can induce many diseases. There are unique advantages of Traditional Chinese Medicine (TCM) to anti-inflammation. Tieguanyin (TGY) is a well-known beverage; the quality is determined by aroma, taste, liquor color, and shape. The volatile compounds produce the flavor of tea, which can be lost with the increase of storage time. TGY has an excellent antiinflammatory effect; its volatile compounds also have an anti-inflammatory impact that is unclear. This study aimed to identify volatile compounds and anti-inflammatory mechanisms within the validity period (TGY1) and the out-of-date (TGY2). Methods: The volatile compounds of TGY1 and TGY2 were analyzed with headspace solid-phase microextraction (HS-PME) and identified by Gas chromatography-mass spectrometry (GC-MS). The percentage of volatile compounds was calculated by the peak area normalization method. The compounds of the targets were obtained from the Traditional Chinese Medicine Systems Pharmacology (TCMSP), PubChem Database, and Swiss Target Prediction database. Next, the disease potential targets were screened by the GeneCards database, Online Mendelian Inheritance in Man (OMM) database, and Therapeutic Target Database (TTD). Furthermore, core targets were screened by the Search Tool for the Retrieval of Inter-acting Genes/Proteins (STRING) database. Then, Gene Ontology (GO) analysis and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway analysis of core targets was performed by the ClueGo plugin Cytoscape 3.7.1 software. At last, Autodock vina software performed molecular docking between the main compounds and core targets. Results: Significant differences in volatile compounds and percentage contents in TGY were observed; the 61 volatile compounds in TGY1 and 57 volatile compounds in TGY2 were identified. After excluding the unidentified compounds, a total of 47 volatile compounds were obtained from TGY1 and TGY2. With the use of network pharmacology, 34 core targets and 23 signaling pathways from TGY1, 28 core targets, and 19 signaling pathways from TGY2 were screened. The main common core targets of TGY1 and TGY2 contained MAPK3, TNF, MAPK1, SRC, etc., while the main different core targets included PTGS2, CAT, etc. A total of 12 biological processes are shared by TGY1 and TGY2, among which the cellular response to oxidative stress is the primary biological process. The different biological processes of TGY1 and TGY2 include cellular response to lipopolysaccharide, androgen receptor signaling pathway, etc. There were 14 common signaling pathways in TGY1 and TGY2, among which the thyroid hormone signaling pathway is the main common signaling pathway. The differential signaling pathways in TGY1 and TGY2 included the erbB signaling pathway, Chagas disease, etc. Molecular docking results showed that the ordinand and differential volatile compounds of TGY1 and TGY2 had different binding forces with the core targets. Conclusion: The GC-MS experiment showed significant differences in volatile compounds and percentage contents in TGY1 and TGY2. Network pharmacology indicated that they have anti-inflammatory effects. Besides, they were different in core targets, biological processes, and signaling pathways but shared similar anti-inflammatory mechanisms. Molecular docking results showed that the binding force of the TGY1 compounds to the core target is greater than that of the TGY2. Therefore, expired TGY affects volatile compounds, resulting in differences in the anti-inflammatory mechanism. The study provided a theoretical framework for further development and application of used medicinal and edible species. In addition, the application of expired TGY under safe conditions can also have anti-inflammatory effects. These results shed new light on the rational use of resources.
Keywords: volatile compounds